2004
DOI: 10.1002/nme.1209
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of granular materials by an improved discrete element method

Abstract: SUMMARYIn this paper, we present an improved discrete element method based on the non-smooth contact dynamics and the bi-potential concept. The energy dissipated during the collisions is taken into account by means of restitution coefficients. The interaction between particles is modelled by Coulomb unilateral contact law with dry friction which is typically non-associated: during the contact, the sliding vector is not normal to the friction cone. The main feature of our algorithm is to overcome this difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 19 publications
0
49
0
2
Order By: Relevance
“…(10)- (12) are shown in Figure 4, where, for differentiability, only the distributions under the shear velocity 0.68 m/s are given. From Figure 4, it is indicated that all of the PDFs for absolute values of upwind and downwind horizontal velocities, vertical velocities and resultant velocities follow an exponential density function, whereas, the angular velocities which lie within − -1500 1100 rev/s distribute with a normal density function, and its symmetrical axis is 0.4693 ω = − rev/s.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(10)- (12) are shown in Figure 4, where, for differentiability, only the distributions under the shear velocity 0.68 m/s are given. From Figure 4, it is indicated that all of the PDFs for absolute values of upwind and downwind horizontal velocities, vertical velocities and resultant velocities follow an exponential density function, whereas, the angular velocities which lie within − -1500 1100 rev/s distribute with a normal density function, and its symmetrical axis is 0.4693 ω = − rev/s.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, the cooling method [12] is required to produce an initial sand bed for particle-bed collision simulation. In order to emulate natural sand particle-bed collision, natural sand particles are sampled from sand dune in southern area of the Tengger desert in China, and their particle diameters obey a lognormal distribution (see Figure 2) [13] .…”
Section: Simulation Of Mixed-size Particle-bed Collisionsmentioning
confidence: 99%
“…Here, we have studied the simple case of nondeformable and nonpenetrable particles in two dimensions with the computational programme MULTICOR [Fortin et al 2005]. The coordinates and the Euler rotation angles are the configuration parameters q.…”
Section: Mechanical Resolution By Demmentioning
confidence: 99%
“…This definition involves not only contact forces between grains, but also inertia forces in dynamical situations (see also[20] for the associated DEM simulations).…”
mentioning
confidence: 99%